Crosstalk between microbiome, regulatory T cells and HCA2 orchestrates the inflammatory response in a murine psoriasis model - Schwarz, Agatha; Philippsen, Rebecca; Piticchio, Serena G.; Hartmann, Jan N.; Häsler, Robert; Rose-John, Stefan; Schwarz, Thomas (Frontiers in Immunology, 2023)
The organ-specific microbiome plays a crucial role in tissue homeostasis, among other things by inducing regulatory T cells (Treg). This applies also to the skin and in this setting short chain fatty acids (SCFA) are relevant. It was demonstrated that topical application of SCFA controls the inflammatory response in the psoriasis-like imiquimod (IMQ)-induced murine skin inflammation model. Since SCFA signal via HCA2, a G-protein coupled receptor, and HCA2 expression is reduced in human lesional psoriatic skin, we studied the effect of HCA2 in this model. HCA2 knock-out (HCA2-KO) mice reacted to IMQ with stronger inflammation, presumably due to an impaired function of Treg. Surprisingly, injection of Treg from HCA2-KO mice even enhanced the IMQ reaction, suggesting that in the absence of HCA2 Treg switch from a suppressive into a proinflammatory type. HCA2-KO mice differed in the composition of the skin microbiome from wild type mice. Co-housing reversed the exaggerated response to IMQ and prevented the alteration of Treg, implying that the microbiome dictates the outcome of the inflammatory reaction. The switch of Treg into a proinflammatory type in HCA2-KO mice could be a downstream phenomenon. This opens the opportunity to reduce the inflammatory tendency in psoriasis by altering the skin microbiome.